Geochemical characteristics of basalts from Andaman subduction zone: Implications on magma genesis at intraoceanic back‐arc spreading centres. (22nd October 2018) - Saha, Abhishek; Mudholkar, Abhay V.; Kamesh Raju, K.A.; Doley, Bhagyashee; Sensarma, Simontini
Abstract : This study reports new petrological and geochemical data for the ocean floor volcanic rocks dredged from the back‐arc basin of the Andaman Sea and elucidates their geochemical characteristics and petrogenetic aspects to provide insights into the melt generation processes, oceanic crust emplacement, and tectonomagmatic evolution of the Andaman back‐arc basin. The studied samples are porphyritic basalts with olivine, plagioclase, and clinopyroxene representing the phenocrysts and the groundmass composition marked by plagioclase microlites, granular clinopyroxenes, and glass. Geochemical characteristics of these basalts reflect sub‐alkaline, tholeiitic composition of precursor magma that experienced clinopyroxene‐Ti magnetite fractionation. The overall geochemical trend for these basalts reflects LILE–HFSE–REE depleted MORB‐type chemistry which is modified by input from subduction‐derived components. Pronounced enrichment in selected LREE (Nd) and incompatible fluid‐mobile trace elements like Ba with positive primitive mantle‐normalized La and Sr anomalies in the majority of these basalts are attributed to transport and influx of slab‐dehydrated fluids and sediments into the depleted back‐arc mantle asthenosphere from the dehydrating subducted oceanic lithosphere in the volcanic arc front during initial stage of back‐arc rifting in the Andaman Sea. The studied basalts were derived by 10%–30% partial melting of a heterogeneous spinel lherzolitic mantle at a shallow depth. The chemical heterogeneity of the spinel lherozolite source suggests an enrichment‐depletion history of back‐arc mantle correlatable with the transitional tectonic evolution of the back‐arc basin from an initial rifting to matured spreading stage. The depleted MORB‐type mantle (DMM) beneath a juvenile back arc experienced infiltration of fluids and subduction‐derived components (SDC) from proximal subducting oceanic slab that gradually diminished with increasing distance from the arc and progressive back‐arc spreading. The episodes of melt generation and magma genesis invoke a gradual geodynamic transition from incipient back‐arc rifting to matured back‐arc spreading stages in the tectonomagmatic evolution of the Andaman back‐arc basin system. Oceanic crust generated during the incipient rifting stage sampled arc‐type melts enriched and hydrated by subduction inputs and fluid flux, while oceanic crust formed during matured back‐arc extension stage inherited trace element depleted MORB‐type mantle signatures devoid of subduction influence.